Pengaruh Islamic Financial Literacy, Lifestyle, Dan Self Control Terhadap Financial Management Behavior Pada Mahasiswa - Rahmatang Rahmatang; Elyanti Rosmanidar; Beid Fitrianova Andriani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The purpose of this study was to determine the effect of Islamic financial literacy, lifestyle and self-control on financial management behavior in FEBI UIN Sulthan Thaha Saifuddin Jambi students. The method used is quantitative method, using SPSS 29. The sample in this study were 95 samples of students from class 2020, 2021, and 2022 by distributing questionnaires. The results showed that there was no significant influence between Islamic financial literacy on financial management behavior, with a tcount < ttable value, namely (1.498 < 1.986) or Sig> a (0.05) value, namely 0.137> 0.05. There is a significant influence between lifestyle on financial management behavior, with a tcount> ttable value, namely (2.645> 1.986) or Sig value < a (0.05), namely 0.010 < 0.05. There is a significant influence between self control on financial management behavior, with a tcount> ttable value, namely (5.090> 1.986) or Sig value < a (0.05), namely 0.000 < 0.05. There is a joint influence between the variables of Islamic financial literacy, lifestyle and self control simultaneously on financial management behavior with a value of 0.001 <0.05 and a value of fcount> ftabel (36.916> 3.10.).